The Implementation of Character Education in Shaping Social Development of Students in Private Elementary School of Mazmur 21 Pontianak - Mertika, Mertika; Astuti, Tri Marhaeni Pudji; Rodiyah, Rodiyah (JESS (Journal of Educational Social Studies), 2018)
Character education is not a type of subject, but it is a process of internalization or implanting positive values for students for having good characters. This study aims to analyze the implementation of character education in shaping social development of students, examine the obstacles of the implementation of character education in shaping the social development of students, and finding action plans for optimizing the implementation of character education in shaping students' social development. The method used in this research is a qualitative method. The data analysis is an interactive analysis model, namely, data collection, data reduction, data presentation and data verification. The results showed that the implementation of character education in shaping the social development of students in private elementary school of Mazmur 21 Pontianak in civilizing activities in the form of routine activities, spontaneous activities, exemplary and also conditioning starting in terms of standards and objectives, resources involved, characteristics of implementing organizations, communication, the attitude of the implementers, the social, economic and political environment, as well as the policy performance is good enough. The obstacles to the policy of implementing character education in shaping social development consist of internal factors and external factors of the school and students. The follow-up to overcome the obstacles is given according to the level of violations. It can be in form of correction (reprimand), compensation or punishment. The significane of this study is its contribution to people's thinking about the relation between character education and social development in order to be able to apply character education, both within the family and community.